2021
DOI: 10.3389/fvets.2021.635671
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Study on the Pathology of Peste Des Petits Ruminants and Tissue Distribution of the Virus Following Experimental Infection of Black Bengal Goats

Abstract: We studied the sequential pathology of peste des petits ruminants (PPR) in Black Bengal goats and analyzed virus distribution in tissues and virus shedding following experimental infection with a Bangladeshi isolate of lineage IV PPR virus (PPRV). The early clinical signs like fever, depression, and ocular and nasal discharges first appeared at 4–7 days post-infection (dpi). Three out of eight inoculated goats died at 13, 15, and 18 dpi, and the rest were killed at different time points from 5 to 18 dpi. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 32 publications
4
12
2
Order By: Relevance
“…A recent study showed maximum viral loads of a local Bangladeshi PPRV strain BD/PPRV/2015/1 by qPCR in the duodenum, jejunum, and ileum, the latter showing the highest amount of virus, similar to the results of the present study [21]. During the past years, IHC studies have shown the presence of numerous PPRV strains in the small intestines, confirming the involvement of the mucosal layer (lamina propria, surface, and crypt epithelial cells) as well as of the submucosa layer (Peyer's patches) during infection [22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…A recent study showed maximum viral loads of a local Bangladeshi PPRV strain BD/PPRV/2015/1 by qPCR in the duodenum, jejunum, and ileum, the latter showing the highest amount of virus, similar to the results of the present study [21]. During the past years, IHC studies have shown the presence of numerous PPRV strains in the small intestines, confirming the involvement of the mucosal layer (lamina propria, surface, and crypt epithelial cells) as well as of the submucosa layer (Peyer's patches) during infection [22][23][24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…In our findings, some syncytial cells appeared inside alveoli which were considered pathognomonic for PPRV (Fig 3b). This lesion was consistent with several previous studies (Kumar et al, 2014;Begum et al, 2021;Islam et al, 2021). Small and large intestine revealed fibrinonecrotic enterocolitis characterized by massive necrosis of mucosa accompanied by mononuclear infiltration as well as severe congestion of the submucosal blood vessels (Fig 3 c,d).…”
Section: Clinical Pathological and Molecular Diagnosis Of Peste Des P...supporting
confidence: 93%
“…The alveoli showed edema and alveolar macrophages. This finding was parallel to Troung et al, (2014) and Begum et al, (2021). In our findings, some syncytial cells appeared inside alveoli which were considered pathognomonic for PPRV (Fig 3b).…”
Section: Clinical Pathological and Molecular Diagnosis Of Peste Des P...supporting
confidence: 83%
See 1 more Smart Citation
“…Also, passages in cell cultures can affect the degree of pathogenicity of an isolate [ 21 ]. Upon infection, PPRV can be found in both lymphoid tissue (spleen, tonsil, mesenteric, sub-maxillary, bronchial, retropharyngeal and pulmonary lymph nodes) and non-lymphoid tissue (nostrils, trachea, abomasum, jejunum, ileum, cecum, lung, intestine, liver, kidney and heart) [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%